2007
DOI: 10.1097/mao.0b013e3180dca1a3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ciprofloxacin/Dexamethasone and Ofloxacin on Tympanic Membrane Perforation Healing

Abstract: HYPOTHESIS:: Exposure to ciprofloxacin/dexamethasone, but not ofloxacin, prolongs tympanic membrane (TM) healing. BACKGROUND:: Exposure to hydrocortisone has been shown to delay TM wound healing. No published studies have compared the effects of ciprofloxacin/dexamethasone and ofloxacin on TM healing. METHODS:: Noninfected TM perforations were created in 30 rats. The rats were split into three groups, and ciprofloxacin/dexamethasone, ofloxacin, or isotonic sodium chloride solution drops were instilled for 8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 10 publications
3
27
0
3
Order By: Relevance
“…Our two recent studies demonstrated that moist perforations with bloody or watery otorrhoea significantly shortened the closure time and improved the closure rate versus dry perforations . In addition, previous studies found that topical antibiotic treatment did not cause TMPs to persist . These findings prompted us to design a clinical study to assess whether a moist eardrum environment resulting from only the topical application of sterile and non‐ototoxic ear drops could accelerate eardrum healing and improve the closure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our two recent studies demonstrated that moist perforations with bloody or watery otorrhoea significantly shortened the closure time and improved the closure rate versus dry perforations . In addition, previous studies found that topical antibiotic treatment did not cause TMPs to persist . These findings prompted us to design a clinical study to assess whether a moist eardrum environment resulting from only the topical application of sterile and non‐ototoxic ear drops could accelerate eardrum healing and improve the closure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (11,12) have shown that oto-topical ciprofloxacin-dexamethasone administration delays TM healing in animal models. These studies did not examine TM healing in the presence of AOM, which results in a more robust healing response (13) and a reduced risk of persistent perforation (14).…”
mentioning
confidence: 97%
“…Despite the beneficial anti‐inflammatory effects of corticosteroids, there are potential negative effects on corneal healing, which frequently preclude their use in equine ulcerative keratitis. Corticosteroids have been associated with a delayed repair in several nonocular tissues . Specific to ophthalmology, corticosteroids have been found to retard corneal epithelial defect closure and contribute to lower corneal stromal cell density in a dose‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids have been associated with a delayed repair in several nonocular tissues. [5][6][7] Specific to ophthalmology, corticosteroids have been found to retard corneal epithelial defect closure and contribute to lower corneal stromal cell density in a dose-dependent manner. [8][9][10][11] Additionally, in vitro stimulation of corticosteroid receptors with the potent synthetic corticosteroid dexamethasone stimulates proliferation of human keratocytes, but simultaneously induces apoptosis and necrosis in these cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation